Three new Fridericia species (Oligochaeta, Enchytraeidae) from Transylvania, Romania - Boros, Gergely; Dózsa-Farkas, Klára (Zootaxa, 2015)
We give descriptions of three new Fridericia species (Enchytraeidae, Oligochaeta) from Transylvania, Romania. Fridericia transylvanica sp. n. is a large-sized worm with a maximum of 4 chaetae per bundle. The spermathecae are separate entally and have two sac-like diverticula bent distad with the ampulla forming a common U-shaped sperm-containing chamber. The species was found not only in the Transylvanian Plateau but also in different regions of the Carpathians in Romania and Serbia. Fridericia gyromonodactyla sp. n. is medium-sized with a maximum of 3 chaetae per bundle. There are only four pairs of preclitellar nephridia. The spermathecal ectal duct is contractile and shorter than the body diameter; each ampulla has only one diverticulum, elongate and coiled, and there is one sessile gland at the orifice. Fridericia longeaurita sp.n. is large-sized with 4(5) chaetae per preclitellar bundle but only two or one in postclitellar bundles. The spermathecal ectal duct is shorter than the body diameter, with one small and sessile ectal gland at the orifice. Each ampulla has two long, ear-shaped, and sac-like diverticula. None of the three species were rare at the sites where they occurred.